Assessment of Direct and Indirect Current Control Techniques Applied to Active Power Filters - Adel, Mohamed; Kandil, Tarek (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: In this paper, an assessment of active power filter (APF) performance is presented under direct and indirect current control schemes through on-line compensation theory. Methods: Conventional Direct Current Control (DCC) measures both load current and filter current beside source and DC-link voltages, while Indirect Current Control (ICC) measures only source current beside voltage measurements. Both DCC and ICC control algorithms are implemented using 80C196KC low-cost microcontroller. Results: The performance parameters of APF are compared under two methods, and it is assigned that ICC gives a better performance with lower cost due to reduced number of sensors. The DC-link output voltage is controlled through simple PI-controller, and the PWM switching signals required by APF power circuit is obtained by hysteresis current controller. Conclusion: The comparative simulation and experimental results exhibit that performance of APF due to ICC scheme is superior than DCC one.
Keywords: direct current control